Empathetic communication: A new paradigm in classroom management - Yasnita, Yasnita; Hakam, Ahmad; Tertia, Chanisa Putri; Tarigan, Abdul Rohman (Universitas Negeri Yogyakarta, 2025)
The inspiration for this investigation comes from a new classroom management trend centred around providing students with assistance and guidance to encourage them to be disciplined, to learn, and to participate in class. Within this context, teachers serve as guides and facilitators rather than external controllers of the students' actions. This investigation aims to determine how empathetic communication helps foster more inclusive learning environments and how it influences student behaviour and academic achievement. As a new paradigm in classroom management, compassionate communication is the study's focus. Interviews, observations, and surveys were combined to conduct the study using a mixed-method approach. The Greater Jakarta region's public and private schools, ranging from elementary to vocational levels, provided data collected from 161 respondents and eight teachers. The study results emphasise that teachers who communicate with empathy make students feel more at ease, more willing to share their thoughts, and more inclined to participate actively in class. One of the practical implications is the necessity of teacher training programs that focus on the development of empathetic communication skills to improve classroom management.